2021
DOI: 10.1002/hyp.14183
|View full text |Cite
|
Sign up to set email alerts
|

Lateral terrestrial water flow contribution to summer precipitation at continental scale – A comparison between Europe and West Africa with WRF‐Hydro‐tag ensembles

Abstract: It is well accepted that summer precipitation can be altered by soil moisture condition. Coupled land surfaceatmospheric models have been routinely used to quantify soil moistureprecipitation feedback processes. However, most of the land surface models (LSMs) assume a vertical soil water transport and neglect lateral terrestrial water flow at the surface and in the subsurface, which potentially reduces the realism of the simulated soil moistureprecipitation feedback. In this study, the contribution of lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 83 publications
1
31
0
Order By: Relevance
“…These estimates of continental recycling appears to be high compared to previous estimates for other African regions (e.g., Arnault et al., 2021), which might point to potential biases in the Lagrangian source analysis. However, a previous intercomparison study between different methodologies by Winschall et al.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…These estimates of continental recycling appears to be high compared to previous estimates for other African regions (e.g., Arnault et al., 2021), which might point to potential biases in the Lagrangian source analysis. However, a previous intercomparison study between different methodologies by Winschall et al.…”
Section: Resultsmentioning
confidence: 50%
“…These estimates of continental recycling appears to be high compared to previous estimates for other African regions (e.g., Arnault et al, 2021), which might point to potential biases in the Lagrangian source analysis. However, a previous intercomparison study between different methodologies by Winschall et al (2014) has shown that, at least for one case study, our trajectory method yields similar results as other numerical water tagging approaches and that the methodological uncertainties associated with the latter can also be large.…”
Section: Moisture Sourcesmentioning
confidence: 50%
“…The choice of WSM6, ACM2, Noah-MP, and waiving of cumulus parameterization is a constraint of WRF-Hydro-iso in its current version. It is noted that this physics setup with a grid-spacing of 5 km proved to give reasonable results for summer precipitation in Europe and West Africa (Arnault et al, 2021).…”
Section: Model Setupmentioning
confidence: 75%
“…As in Arnault et al (2021), the version of WRF-Hydro-tag considered in this study is based on the WRF version 4.0 and the hydrological module of WRF-Hydro version 5.0, and the selected physics parameterization options are the six-class WSM6 microphysics scheme of Hong and Lim (2006), the ACM2 atmospheric turbulence scheme of Pleim (2007), and the Noah-MP community Noah land surface model (LSM) with multi-parameterization options of Niu et al (2011). WRF-Hydro-tag can be run with subsurface, overland, and channel flow routing, as well as a bucket model to estimate baseflow (Gochis et al, 2018).…”
Section: About Wrf-hydro-tagmentioning
confidence: 99%
“…Indirectly, indications of possible hydrological impact produced by larger‐scale (continental) application of a fully coupled approach were provided by Arnault et al (2021), who, however, detected a slight precipitation increase. The atmosphere‐land‐ocean coupled system applied by Lewis and Dadson (2021) over the whole United Kingdom showed its ability to predict broad‐scale features of river streamflow even without using proper calibration procedures.…”
Section: Contributionsmentioning
confidence: 99%